Desfechos maternos e fetais em gestantes com adenomas hipofisários e/ou síndrome de Cushing: revisões sistemáticas e meta-análises - Bandeira, Diego Barata [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
INTRODUCTION: Pituitary adenomas account for up to 15% of intracranial neoplasms and, although they may impair fertility, many women with this diagnosis are able to conceive. Pregnancy in women with these tumors raises clinical concerns regarding the potential mutual impacts between pituitary disease and the physiological changes of gestation. OBJECTIVE: To evaluate maternal and fetal outcomes in pregnant women with pituitary adenomas and/or Cushing’s syndrome. METHODS: Five systematic reviews were conducted following the Joanna Briggs Institute methodology for etiology and risk, including observational studies of pregnant women diagnosed with pituitary adenoma and/or Cushing’s syndrome. The outcomes evaluated included the frequency of tumor and hormonal control; gestational diabetes or worsening of pre-existing diabetes; hypertension; preterm birth; headache; tumor growth or apoplexy; visual disturbances; spontaneous abortion; and, among neonatal outcomes, perinatal mortality, low birth weight, congenital malformations, and small for gestational age infants. Searches were conducted in Embase, Medline, CENTRAL and LILACS databases. Two independent reviewers selected studies, extracted data, and assessed the risk of bias. For dichotomous outcomes, proportional meta-analyses were performed using STATA 18, employing the metaprop_one command. RESULTS: For acromegaly, 19 studies were included, comprising 273 pregnancies in 211 women. The overall rate of clinical disease control during pregnancy was 62%, and tumor growth was reported in 9% of cases. The frequency of gestational diabetes or worsening of pre-existing diabetes was 9%, hypertensive disorders occurred in 6% of pregnancies, preterm birth in 9%, and spontaneous abortion in 4%. For prolactinoma, 52 studies were included, encompassing 2,544 pregnancies in 1,928 women. Dopamine agonists were used at conception in 97% of cases, and treatment was continued or reintroduced during pregnancy in 6%. The overall frequency of spontaneous abortion was 10%, preterm birth 3%, congenital malformations 2%, perinatal mortality 2%, and low birth weight 6%. For Cushing’s syndrome, 22 studies comprising 380 pregnancies in 200 women were analyzed. The overall rate of spontaneous abortion was 6%, preterm birth 36%, gestational or worsened diabetes 23%, and hypertensive disorders 39%. Perinatal mortality occurred in 7% and low birth weight in 27% of cases. For clinically non-functioning pituitary adenomas (NFPAs), 5 studies were included, comprising 36 pregnancies in 35 women. Tumor growth occurred in 36% of cases, visual impairment in 20%, and apoplexy in 15%. Preterm birth occurred in 10% and perinatal mortality in 3%. Due to the rarity of TSH-secreting adenomas (TSHomas) during pregnancy, only 11 case reports were identified, totaling 12 pregnancies (including one twin gestation) in 11 women. Among all studies, a single maternal death was reported, occurring in a patient with Cushing’s syndrome. Except for women with Cushing’s syndrome, most pregnancies occurred in patients with adequately controlled pituitary disease prior to conception. CONCLUSION: Regarding maternal and fetal outcomes in women who became pregnant after being diagnosed with a pituitary disorder, it was observed that, except for cases of Cushing’s syndrome, complication rates were similar to those reported in the general obstetric population. In contrast, among women with Cushing’s syndrome, most had uncontrolled hypercortisolism at conception and throughout pregnancy, which may have contributed to the higher frequency of preterm birth, hypertension, and diabetes mellitus observed in this group. PROSPERO registrations: PROSPERO CRD42021283757, CRD42020151416, CRD42024597682, CRD42024598697, and CRD420251065843.
Management of pregnant women with pituitary adenomas and Cushing’s syndrome and their implications for maternal-fetal outcomes: systematic reviews and Meta-Analyses
Keywords: Gravidez; Tumores hipofisários; Acromegalia; Prolactinoma; Doença de Cushing; Adenoma; Tireotropinoma; Revisão Sistemática; Meta-análises; Hipersecreção hipofisária de ACTH; Revisão